Resisting the pandemic: Better stories and innovation in times of crisis (Peter Lang International Academic Publishers, 2024)
In an era marked by profound disparities, this book explores the significant ways the pandemic has deepened gender inequalities in the labor, education, and health sectors. Through a rigorous analysis within the RESISTIRÉ EU funded project framework, it highlights innovative scientific and social methodologies that have emerged to challenge these inequalities. Structured into nine chapters, the work synthesizes insights gained from extensive evaluations of public policies and grassroots initiatives across Europe, offering ‘better stories’ and practices that encapsulate transformative potentials in crisis response.